ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM MEWUJUDKAN MERDEKA BELAJAR - Rohyadi, Edi; Ila Rosmilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses the leadership role of school principals in realizing an independent learning curriculum in educational units. The independent learning curriculum rolled out by the Ministry of Education, Culture, Research and Technology aims to create a learning environment that is more adaptable and innovative in line with current trends by providing greater freedom to students and teachers in the learning process. The method used in this research is Systematic Literature Review or SLR by analyzing 10 articles from national journals published in the last 2 years, namely 2022-2023, with the topic of discussing school principal leadership and the implementation of the independent learning curriculum. The results of this research are that the leadership of the school principal is a key and significant factor in realizing an independent learning curriculum in schools. The school principal plays a very important role in inspiring and empowering teachers to implement learning that is meaningful and relevant to current developments, preparing adequate facilities and infrastructure, encouraging active participation from students and parents in supporting all school programs, and collaborating with stakeholders. This research can provide information for school principals about leadership patterns and styles that can be applied according to the situation and conditions of the school.